Randomized controlled trial of standard closure of a stoma site vs biological mesh reinforcement: study protocol of the ROCSS trial. (2nd February 2018) - ,
Abstract: Background: Closure of complex and contaminated abdominal wounds is challenging and carries risks, including wound dehiscence and incisional hernia. Hernia formation at closed stoma sites occurs in up to 30% of patients. Use of biological meshes in these situations may provide a safe method of reducing these complications, especially long‐term incisional hernias. Method: The Reinforcement of Closure of Stoma Site (ROCSS) study is a Phase III multicentre randomized controlled trial (RCT) with an internal feasibility study. The primary objective of ROCSS is to assess whether a biological mesh (collagen tissue matrix) reduces the incidence of clinically detectable stoma closure site hernias at 2 years compared with standard closure techniques. Patients will be randomized in a 1:1 ratio to either standard suture (nonmesh) closure or closure with an intra‐abdominal biological mesh reinforcement. Patients and outcome assessors are masked to treatment allocation. ROCSS aims to recruit 560 patients, with an option to recruit to 790 patients to increase power. The primary outcome measure is the occurrence of clinically detectable hernias years 2 years postrandomization. The secondary outcome measures are the radiological hernia rate at 1 year, incidence of symptomatic hernia, the surgical complication/re‐intervention rate, quality of life, postoperative pain and cost–benefit analysis. Discussion: ROCSS is a multicentre RCT assessing the placement of a biological mesh at the site of stoma closure on clinical hernia rate. Our hypothesis is that reinforcing the stoma closure site with a collagen mesh is superior to the standard technique in reducing the risk of herniation at 2 years. These findings could influence future closure of stomas and other complex and/or contaminated abdominal wounds in settings around the world.